Medicinska sestra in humor na delovnem mestu - Jerčič, Lilijana (Obzornik zdravstvene nege, 2004)
The article presents the theme of humor and laughter as a means of fighting burn-out and stress at work place. The first part of the article presents theoretical definition of humor and laughter in professional and everyday life, as well as sources, function and effects of stress and burn-out syndromein nurses. The second part of the article presents a research study the aim of which was to ascertain the effect of humor on work quality and workelimate and on needs fnr education. The discussion and conclusion parts present conclusions and propositions for building in humor in everyday professional and private life of nurses.
Keywords: ankete; Burnout, Professional; Delovno mesto; humor; Humor in šale; humour; Izgorevanje poklicno; Job Satisfaction; laughter; Medicinska sestra-bolnik, odnosi; medicinske sestre; Nurse-Patient Relations; Nursing Care; poklic; poklicni stres; Poklicno zadovoljstvo; Questionnaires; smeh; stres; Stres psihološki; Stress, Psychological; Wit And Humor; Workplace; Zdravstvena nega